BUBR1 expression in benign oral lesions and squamous cell carcinomas: Correlation with human papillomavirus - Lira, Regia C. P.; Miranda, Fabiana A.; Guimaraes, Marcia C. M.; Simoes, Renata T.; Donadi, Eduardo A.; Soares, Christiane P. [UNESP]; Soares, Edson G. (Spandidos Publ Ltd, 2010)
Oral squamous Cell carcinoma (OSCC) is the most common head and neck cancer. Only in Brazil, the estimate is for 14,160 new cases in 2009. HPV is associated with increasing risk of oral cancer, but its role in carcinogenesis is still controversial. BUBR1, all important protein in the mitotic spindle assembly checkpoint (SAC), has been associated with some virus-encoded proteins and cancer. The aim of the present study was to evaluate the expression of BUBR1 in non-malignant oral lesions and OSCC with and without metastasis associated with HPV infection. We performed immunohistochemistry for BUBR1 in 70 OSCC biopsies divided into three groups (in situ tumors, invasive tumors without metastasis and invasive tumors with metastasis) with their respective lymph nodes from samples with metastasis and in 16 non-malignant oral lesions. PCR was performed in order to detect HPV DNA. Significantly higher BUBR1 expression associated with shorter survival (p=0.0479) was observed in malignant lesions. There was also it significant correlation (r=1.000) with BUBR1 expression in lesions with metastasis and their lymph nodes. Ninety percent of OSCC and 100% of benign lesions were HPV positive. HPV16 and HVP18 were present in 13 and 24% of HPV-positive OSCC samples, respectively. HPV was more prevalent (76%) in samples with a high BUBR1 expression and the absence of viral DNA had no influence oil BUBR1 expression. These findings suggest that HPV could be associated with overexpression of BUBR1 in OSCC. but not in benign oral lesions.
Keywords: BUBR1; HPV; oral squamous cell carcinoma